0466 Labour market and health trajectories during periods of economic recession and expansion in the united states, 1988–2011. (21st August 2017) - Fan, Jonathan; Amick, Benjamin; Richardson, Lindsay; Scott-Marshall, Heather; McLeod, Chris
Abstract : Objectives: Negative labour market experiences are associated with worse health outcomes, although little research has examined health effects of trajectories over time. This study examined associations between labour market and health (LMH) trajectories in the US between 1988 and 2011 and and whether associations differed across four macroeconomic periods defined by contraction or expansion. Methods: Working-age cohorts were derived for each period using data from the Panel Study of Income Dynamics. Cohorts started from a baseline state of employment/good health, and were followed over time to characterise LMH trajectories. Modified Poisson regression provided relative risks (RR) with robust 95% CIs for the association between trajectories. Results: LM trajectories ending in unemployment (RRs 1.7–2.5 across periods) or inactivity (RRs 2.3–3.2) had a greater risk of worse health trajectories, compared to stable employment. Individuals recovering into employment following a period of inactivity experienced a greater risk of worse health (RR s 1.6–2.1). There were persistent health-gradients across trajectories, with stable-employed individuals having the highest probability of remaining in good health, and 'LM exit' trajectories having the lowest probability. Overall relationships were consistent across the four periods. Conclusions: The increased likelihood of having worse health among unemployed/inactive individuals, yet attenuated risk among those recovering into employment following these intermediary states, suggests that health outcomes are not only dependent on the LM end-state, but also on the distinct pattern over time. Findings suggest that the contextual economic period has limited impact on these overall relationships, although future research might incorporate methodological frameworks with direct measures of the social-economic context.